“Too much medicine”: Insights and explanations from economic theory and research - Hensher, M.; Tisdell, J.; Zimitat, Craig (Pergamon Press Ltd., 2017)
Increasing attention has been paid in recent years to the problem of “too much medicine”, whereby patients receive unnecessary investigations and treatments providing them with little or no benefit, but which expose them to risks of harm. Despite this phenomenon potentially constituting an inefficient use of health care resources, it has received limited direct attention from health economists. This paper considers “too much medicine” as a form of over-consumption, drawing on research from health economics, behavioural economics and ecological economics to identify possible explanations for and drivers of overconsumption. We define overconsumption of health care as a situation in which individuals consume in a way that undermines their own well-being. Extensive health economics research since the 1960s has provided clear evidence that physicians do not act as perfect agents for patients, and there are perverse incentives for them to provide unnecessary services under various circumstances. There is strong evidence of the existence of supplier-induced demand, and of the impact of various forms of financial incentives on clinical practice. The behavioural economics evidence provides rich insights on why clinical practice may depart from an “evidence-based” approach. Moreover, behavioural findings on health professionals’ strategies for dealing with uncertainty, and for avoiding potential regret, provide powerful explanations of why overuse and overtreatment may frequently appear to be the “rational” choice in clinical decision making, even when they cause harm. The ecological economics literature suggests that status or positional competition can, via the principal-agent relationship in health care, provide a further force driving overconsumption. This novel synthesis of economic perspectives suggests important scope for interdisciplinary collaboration; signals potentially important issues for health technology assessment and health technology management policies; and suggests that cultural change might be required to achieve significant shifts in clinical behaviour.